Дизайн высокоспиновых молекул - Третьяков Е. В.; Заякин И. А.; Зимина А. М.; Грицан Н. П.; Петунин П. В. Павел Васильевич; Постников П. С. Павел Сергеевич; Богомяков А. С.; Романенко Г. В. (2025, 2025)
Текстовый файл